(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Stress and lifestyle disorders are the most dominating issues faced by people in present scenario which leads to deterioration health of individuals. One such burning issue which is gearing up continuously is male infertility. One of the most common causes of male infertility has been found to be Oligozoospermia which means semen with a low concentration of sperm. For many decades, sperm concentration of less than 20 million spermml, low or Oligospermic but recently WHO has reassessed sperm criteria and established a lower reference point, less than 15 million spermml. Other than sperm count physical examination of semen is also essential which includes observation of its volume, colour, turbidity, liquefaction, viscosity, morphology and mortality. As per Ayurveda, Oligozoospermia can be correlated to Ksheen Shukra. Shukra is considered as one of the seven Dhatus and assigned with the function of bestowing the progeny. Even though none of the standard Ayurvedic Texts have mentioned about the count of sperm or it’s motility but clearly mentioned the quality of semen in the form of “Shuddh Shukra Lakshanas”. According to Acharya Sushrut Shuddh Shukra is White as Sphatik, Drava, Snigdh, Madhura and smells like Honey. For ruling out the cause of infertility Shukra Dhatu is examined and observed in Semen Analysis.